Cohort Profile:The Danish National Cohort Study of Effectiveness and Safety of SARS-CoV-2 vaccines (ENFORCE) - Kasper Karmark Iversen; Henrik Nielsen; Isik S Johansen; Lykke larsen; Lothar Wiese; Thomas Benfield; Lene Surland Knudsen; Lars Østergaard; Joanne Reekie; Ole S Søgaard; Jens Lundgren; Britta Tarp; et al. (BMJ Open)
Purpose The ENFORCE cohort is a national Danish prospective cohort of adults who received a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine as part of the Danish National SARS-CoV-2 vaccination programme. It was designed to investigate the long-term effectiveness, safety and durability of SARS-CoV-2 vaccines used in Denmark.Participants A total of 6943 adults scheduled to receive a SARS-CoV-2 vaccine in the Danish COVID-19 vaccination programme were enrolled in the study prior to their first vaccination. Participants will be followed for a total of 2 years with five predetermined follow-up visits and additional visits in relation to any booster vaccination. Serology measurements are performed after each study visit. T-cell immunity is evaluated at each study visit for a subgroup of 699 participants. Safety information is collected from participants at visits following each vaccination. Data on hospital admissions, diagnoses, deaths and SARS-CoV-2 PCR results are collected from national registries throughout the study period. The median age of participants was 64 years (IQR 53–75), 56.6% were women and 23% were individuals with an increased risk of a serious course of COVID-19. A total of 340 (4.9%) participants tested positive for SARS-CoV-2 spike IgG at baseline.Findings to date Results have been published on risk factors for humoral hyporesponsiveness and non-durable response to SARS-CoV-2 vaccination, the risk of breakthrough infections at different levels of SARS-CoV-2 spike IgG by viral variant and on the antibody neutralising capacity against different SARS-CoV-2 variants following primary and booster vaccinations.Future plans The ENFORCE cohort will continuously generate studies investigating immunological response, effectiveness, safety and durability of the SARS-CoV-2 vaccines.Trial registration number NCT04760132.